HYDRODYNAMICS AND HEAT AND MASS TRANSFER IN MUSHROOM-SHAPED HEADS OF THERMOCHEMICAL PLUMES - A. G. Kirdyashkin; A. A. Kirdyashkin (Геодинамика и тектонофизика, 2018)
The model of a thermochemical mantle plume is described. The scheme of origination of the plume from the core-mantle boundary is presented. The basic ratios for determining the thermal power and the diameters of thermochemical plumes are given. After eruption of the melt from the plume conduit to the surface, melting occurs along the base of the crustal block above the plume roof, resulting in the formation of a mushroom-shaped head of the plume, which means that a large intrusive body (deep-rooted batholith) is formed. The relative thermal power of such plumes is 1.9<Ka<10. Based on the laboratory and theoretical modeling results, we present the thermal and hydrodynamic structure of the thermochemical plume with the mushroom-shaped head. The parameters of some plumes, that are responsible for formations of batholiths in North Asia, are estimated from the geological data, including the age intervals and the extent of magmatism. Relying on the model of the flat horizontal liquid layer, hydrodynamics and heat transfer of the mushroom-shaped plume head are considered. The variations in temperature and flow velocity in the melt of the plume head are assessed. The compositional changes in the melt of the plume head are determined by stages: (1) after settling of refractory minerals; (2) after settling of plagioclase in the melt resulting from the first stage. The tables show the calculation data, including the weight contents of oxides and the normative compositions for the melts at Tmelt=1410 °C and Tmelt=1380 °C. The thickness of the residual melt is estimated for the case of the Khentei plume. Its head’s thickness (l) is equal to the plume conduit diameter (d): l=d=29 km. The proposed model of the plume with the mushroom-shaped head was used to calculate the normative composition of the melt with a chemical composition similar to that of normal granites.